Impact of pharmacist active consultation on clinical outcomes and quality of medical care in drug-induced liver injury inpatients in general hospital wards: A retrospective cohort study - Li, Dongxuan; Dong, Jie; Xi, Xin; Huang, Guili; Li, Wenjun; Chen, Cheng; Liu, Jun; Du, Qian; Liu, Songqing (Frontiers in Pharmacology, 2022)
The utility of pharmacist consultation for drug-induced liver injury (DILI) management has not been explored. This retrospective cohort study evaluated the impact of a pharmacist active consultation (PAC) service on the management and outcome in patients with DILI. Consecutive patients meeting clinical biochemical criteria for DILI were enrolled at a tertiary teaching hospital between January 1, 2020 and April 30, 2022. The Roussel Uclaf Causality Assessment Method was used to assess causality between drug use and liver injury for each suspected DILI patient. Included patients were grouped according to whether they received PAC, and a proportional hazards model with multivariate risk adjustment, inverse probability of treatment weighting (IPTW) and propensity score matching (PSM) was used to assess DILI recovery. In the PSM cohort, the quality of medical care was compared between PAC and no PAC groups. A total of 224 patients with DILI (108 who received PAC and 116 who did not) were included in the analysis. Of these patients, 11 (10%) were classified as highly probable, 58 (54%) as probable, and 39 (36%) as possible DILI in the PAC group, while six patients (5%) were classified as highly probable, 53 (46%) as probable, and 57 (49%) as possible DILI in the no PAC group (P=0.089). During patient recovery, PAC was associated with a ~10% increase in the cumulative 180-day recovery rate. The PAC group had a crude hazard ratio (HR) of 1.73 (95% confidence interval [CI]: 1.23–2.43, P=0.001) for DILI 180-day recovery, which remained stable after multivariate risk adjustment (HR=1.74, 95% CI: 1.21–2.49, P=0.003), IPTW (HR=1.72, 95% CI: 1.19–2.47, P=0.003), and PSM (HR=1.49, 95% CI: 1.01–2.23, P=0.046). In the PSM cohort, PAC was more likely to identify suspect drugs (90% vs. 60%, P<0.001) and lead to timely withdrawal of the medication (89% vs. 57%, P<0.001). Thus, PAC is associated with a better quality of medical care for patients with DILI and can improve patient outcomes.